Mycotoxins and Their Metabolites in Humans and Animals - Weidenbörner, Martin. (Springer US : Imprint: Springer, 2011)
Due to the serious spoilage and health issues the presence of mycotoxins can cause, it is imperative that corresponding scientists, health institutions, and the food and feed industries have a more qualified understanding of mycotoxins in living things. To this end, Mycotoxins and Their Metabolites in Humans and Animals provides an excellent resource. The present book complements the series of the author’s previous books, Mycotoxins in Feedstuffs and Mycotoxins in Foodstuffs, in that it is a review of the literature to create a comprehensive reference for mycotoxin levels. It focuses on the natural and artificial incidence of mycotoxin(s) in humans and animals. Each entry includes contamination, concentration rate, mostly mean mycotoxin concentration of organs (human and animal), and country of origin of the sample.